Short selling and stock returns: evidence from the UK - Mohamad, Azhar; Jaafar , Aziz; Hodgkinson , Lynn; Wells, Jo (2011)
This paper examines the information content of short interest by investigating whether firms that experience significant daily increases in short interest subsequently experience negative abnormal returns. Using UK daily short interest data for the period September 2003 to April 2010, we find a significant negative cumulative average abnormal return of 1.48% for valuation short stocks for the first 15 days post-publication of short interest data. This result suggests that short interest has informational content consistent with the Diamond and Verrecchia (1987) hypothesis: unusually large increases in short interest are followed by periods of negative abnormal returns.